THE OCCURRENCE OF CONTRACTURE AND THE SEVERITY OF BURN INJURIES AMONG BURN PATIENTS TREATED AT DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA (2020-2022) - Hamiseno, Gifta Marshanda Qanitah; Iswinarno Doso Saputro; Diah Mira Indramaya; Lobredia Zarasade (Jurnal Rekonstruksi dan Estetik, 2024)
Highlights: A robust association was observed between total body surface area (TBSA) and burn injuries, except in the case of elderly individuals. The duration of hospitalization is significantly associated with the occurrence of contracture. Abstract: Introduction: Burn injuries are a worldwide issue and can happen for many reasons, often causing skin damage that leads to deformities and movement difficulties. Many burn patients, up to 50%, experience contractures, which limit movement in areas such as the shoulders, wrists, and torso. Proper management through medicine, surgery, and therapy is crucial for helping these patients. Research at Dr. Soetomo General Academic Hospital is focused on studying the frequency of contractures after burn injuries to improve treatment and prevention methods. Methods: The research used descriptive analytics and gathered data from the Burn Unit at Gedung Bedah Pusat Terpadu (GBPT) and the Plastic Surgery Polyclinic at Dr. Soetomo General Academic Hospital in Surabaya. The study examined 40 eligible patients and assessed variables including burn severity, affected body area, and hospitalization duration. Results: The results showed that the average age of patients was 26.30 years, with 70% of them being male. Only 5% of patients had other health problems, mainly related to hormones. Most burns were caused by fire (37.5%), and many were second-degree burns (42.5%). The percentage of the body affected by burns varied by age: children had around 9.86%, adolescents had around 15.96%, and adults had around 5.25%. Most injuries were on the left arm (67.5%), and many patients stayed in the hospital for a long time (67.5%). Conclusion: All patients developed contractures following burns, irrespective of burn severity. There was a correlation between burn size and severity, except among older patients. Additionally, a notable association was observed between contracture occurrence and prolonged hospitalization.